2020
DOI: 10.1097/sla.0000000000004635
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Affordable Care Act on Trauma Outcomes in At-Risk Groups

Abstract: Objective: Analyze the impact of the Affordable Care Act (ACA) on trauma outcomes at a population level and within at-risk subgroups. Background: Trauma disproportionately affects the uninsured. Compared to the insured, uninsured patients have worse functional outcomes and increased mortality. The goal of the ACA was to increase access to insurance. Methods: An interrupted time series was conducted using data from the National Inpatient Sample database between 2011 and 2016. Data from Alberta, Canada was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…10 Conversely, a study using NIS data from 2011 to 2016 and a Canadian province as a control found that Medicaid expansion was associated with a greater reduction in trauma in-hospital mortality compared to non-expansion states. 1 The improved survival of severely injured individuals may be attributed to several key factors. Advances in medical technology, such as advanced imaging and damage control surgery, enable more accurate and effective diagnosis and treatment of severe injuries.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…10 Conversely, a study using NIS data from 2011 to 2016 and a Canadian province as a control found that Medicaid expansion was associated with a greater reduction in trauma in-hospital mortality compared to non-expansion states. 1 The improved survival of severely injured individuals may be attributed to several key factors. Advances in medical technology, such as advanced imaging and damage control surgery, enable more accurate and effective diagnosis and treatment of severe injuries.…”
Section: Discussionmentioning
confidence: 99%
“…7 In-hospital mortality due to trauma, which is sensitive to the timeliness of care, external factors, and resource availability, serves as a metric for assessing the effectiveness of healthcare interventions, the performance of healthcare facilities, and healthcare policies. 1,2,8 Studies have demonstrated that Medicaid expansion has led to notable improvements in various healthcare aspects, including enhanced access to care, post-discharge rehabilitation services, and hospital financial stability. 4,[9][10][11] Nonetheless, the existing literature on the impact of ACAME on trauma in-hospital mortality presents conflicting findings.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations